Perception of The Community of Tegowanu Wetan Village, Tegowanu District, Grobogan District Towards The Tradition of Cucuk Lampah In Traditional Javanese Weddings - Novitasari, Yusita Kurnia (Library of Sultan Agung Islamic University, 2024)
The cucuk lampah tradition is one of the traditions inherited from ancestors which has been passed down from generation to generation in Tegowanu Wetan Village, Tegowanu District, Grobogan Regency. This tradition is believed to repel evil spirits or interference from evil spirits when holding a wedding. Cucuk lampah is played by a man who has an authoritative character like a senopati or kesatriyo. But the cucuk lampah found in Tegowanu Wetan Village is a man whose character resembles a woman in terms of clothing, speaking style and walking style. This research is included in qualitative research and uses field research , namely research carried out by direct observation in the field.The result of this research is that the cucuk lampah tradition is carried out after the bridal panggih ceremony. The cucuk lampah dancer is followed by two bridesmaids , four ayu pagers , 2 satriyo twins , the bride and groom, each bride's parents, siblings, and bridesmaids . The cucuk lampah dancers are also accompanied by music with the aim that the dance matches the rhythm of the music and the group can also follow the movements. Cucuk lampah's cross- gender practice is motivated by people who are starting to get bored with their appearance. The perception of the people of Tegowanu Wetan Village regarding the function of cucuk lampah cross gender , including as a means of friendship, a means of entertainment, a means of economic value, and cultural preservation.Keywords : Community Perception, Tradition, Cucuk Lampah, Cross Gender .